Type specimens of Sphecidae (Hymenoptera, Apoidea) in the Zoological Institute of the Russian Academy of Sciences in St. Petersburg - Danilov, Yuriy N. (Zootaxa, 2016)
The article contains a review of the type specimens of Sphecidae described by E. Eversmann, F. F. Morawitz, F. F. Kohl, V. V. Gussakovskij, V. L. Kazenas, A. S. Menke and Yu. Danilov, and deposited at the Zoological Institute of the Russian Academy of Sciences in St. Petersburg. Altogether 157 type specimens of 56 taxa were examined. Type specimens of Podalonia kozlovii (Kohl, 1906), whose depository was previously unknown, have been located.